(untitled) (Swiss Medical Weekly, 2020)
AIMS OF THE STUDY Clostridioides difficile infection (CDI) is associated with high morbidity, recurrence rates and mortality. We assessed the local epidemiology, treatment outcomes and risk factors for recurrence and mortality. METHODS This was a retrospective study of all adult CDI episodes treated in our tertiary care hospital between 2014 and 2016. Patients were followed up for 60 days, with recurrence and death as endpoints. Antibiotic treatment as well as epidemiological, clinical and laboratory parameters were studied using logistic regression analysis. Risk factors for recurrent CDI (age >70 years, haematological malignancy, chronic kidney disease, severe infection, continued antibiotics other than for CDI, proton pump inhibitor / antacid use) and indicators of severe CDI (temperature ≥38.5°C, leucocytes >15 × 109/l, creatinine increase ≥1.5 × baseline, albumin <25 g/l) were analysed. We considered episodes with ≥2 indicators as severe. RESULTS We identified 210 CDI episodes (66 severe) in 191 patients with a median age of 71 years (interquartile range 59–79). Hypervirulent ribotype 027/NAP1/BI accounted for four episodes (2%). Overall, 176, 30 and 4 patients, respectively, received a first, second and third treatment. Metronidazole was used in 94% of the first episodes and in 73% and 50% of the first and second recurrences, respectively. The recurrence rate after the first metronidazole treatment was 20%. Recurrence rates were higher when ≥2 risk factors were present (25 vs 10%, p = 0.03). The 60-day mortality was 17% (4% attributable to CDI) and increased with the presence of ≥2 indicators of severe CDI. CONCLUSIONS The high 60-day mortality suggests that CDI is a strong indicator of frailty. Metronidazole was associated with low recurrence rates at minimal costs in patients with uncomplicated CDI, but had relevant shortcomings in patients with severe CDI and/or a high risk of recurrence, suggesting that these vulnerable patients might better be treated with oral vancomycin and fidaxomicin, according to the latest guidelines.